Prehospital ultrasound constitutes a potential distraction from the observation of critically ill patients: a prospective simulation study - Yael van der Geest; Luca Marengo; Roland Albrecht; Philipp K. Buehler; Pedro D. Wendel-Garcia; Daniel A. Hofmaenner; Urs Pietsch (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2024)
Abstract Background Prehospital point-of-care ultrasound allows an unstable patient to be rapidly and accurately assessed. However, we are concerned that an excessive focus on the ultrasound device, in an already demanding emergency medical service environment, may distract from patient care, potentially leading to reduced situational awareness and the neglect of other crucial instruments, such as the patient monitor. Thus, in this study, we examined the influence of prehospital ultrasound on situational awareness, by studying the degree to which physicians were distracted from the patient monitor. Methods We observed HEMS physicians in a simulated setting and analysed their gaze behaviour using an eye tracker placed on three areas of interests: the ultrasound device, the patient and the patient monitor. In the course of the experiment, the simulated patient desaturated, which was presented on the patient monitor. The primary outcome was the fraction of gaze distribution across the three areas of interest, while secondary outcomes were different gaze metrics (dwell time, revisits, average duration of visual intake and entry time) on the patient monitor. We then compared the participants who noticed the patient’s deterioration with those who did not. Results In 75% of cases, the severely decreased oxygen saturation went unnoticed during the test. Moreover, the gaze distribution of the two groups differed, with the group that recognised the deterioration focusing longer on the patient monitor (7.8% (95% CI 5–10.7) vs 0.1% (95% CI 0–0.3), p: 0.124). Conclusions The task of performing an ultrasound examination appears to overwhelm some participants and distract them from other aspects of the scenario. Efforts to mitigate distractions and optimise the use of prehospital ultrasound, such as education, a focus on human factors aspects and standardisation, are crucial for maximising the potential benefits of prehospital ultrasound.